No impact of prenatal paracetamol and folic acid exposure on cord blood DNA methylation in children with attention-deficit/hyperactivity disorder - Olstad, Emilie Willoch; Nordeng, Hedvig Marie Egeland; Lyle, Robert; Gervin, Kristina (Frontiers in Genetics, 2023)
Pharmacoepigenetic studies are important to understand the mechanisms through which medications influence the developing fetus. For instance, we and others have reported associations between prenatal paracetamol exposure and offspring DNA methylation (DNAm). Additionally, folic acid (FA) intake during pregnancy has been associated with DNAm in genes linked to developmental abnormalities. In this study, we aimed to: (i) expand on our previous findings showing differential DNAm associated with long-term prenatal paracetamol exposure in offspring with attention-deficit/hyperactivity disorder (ADHD), and (ii) examine if there is an interaction effect of FA and paracetamol on DNAm in children with ADHD. We used data from the Norwegian Mother, Father and Child Cohort Study (MoBa) and the Medical Birth Registry of Norway (MBRN). We did not identify any impact of paracetamol or any interaction effect of paracetamol and FA on cord blood DNAm in children with ADHD. Our results contribute to the growing literature on prenatal pharmacoepigenetics, but should be replicated in other cohorts. Replication of pharmacoepigenetic studies is essential to ensure robust findings and to increase the clinical relevance of such studies.